Admission Serum Bicarbonate Predicts Adverse Clinical Outcomes in Hospitalized Cirrhotic Patients. (18th May 2021) - Schopis, Michael; Kumar, Anand; Parides, Michael; Tepler, Adam; Sigal, Samuel
Abstract : A low serum bicarbonate (SB) level is predictive of adverse outcomes in kidney injury, infection, and aging. Because the liver plays an important role in acid-base homeostasis and lactic acid metabolism, we speculated that such a relationship would exist for patients with cirrhosis. To assess the prognostic value of admission SB on adverse hospital outcomes, clinical characteristics were extracted and analyzed from a large electronic health record system. Patients were categorized based on admission SB (mEq/L) into 7 groups based on the reference range (22–25) into mildly (18–21), moderately (14–17), and severely (<14) decreased groups and mildly (26–29), moderately (30–33), and severely (>30) increased groups, and the relationship of SB category with the frequency of complications (acute kidney injury/hepatorenal syndrome, portosystemic encephalopathy, gastrointestinal bleeding, ascites, and spontaneous bacterial peritonitis) and hospital metrics (length of stay [LOS], admission to an intensive care unit [ICU], and mortality) was assessed. A total of 2, 693 patients were analyzed. Mean SB was 22.9 ± 4.5 mEq/L. SB was within the normal range (22–25 mEq/L) in 1, 072 (39.8%) patients, and 955 patients (36%) had a low SB. As the SB category decreased, the incidence of complications progressively increased (p < 0.001 ). Increased MELD-Na score and low serum albumin also correlated with frequency of complications (p < 0.001 ). As the SB category decreased, LOS, ICU admission, and mortality progressively increased (p < 0.001 ). On multivariate analysis, the association of decreased SB with higher odds of complications, LOS, ICU admission, and mortality persisted. Conclusion . Low admission SB in patients with cirrhosis is associated with cirrhotic complications, longer LOS, increased ICU admissions, and increased hospital mortality.